1993
DOI: 10.1063/1.109466
|View full text |Cite
|
Sign up to set email alerts
|

Terracing and step bunching in interfaces of molecular beam epitaxy-grown (Al)GaAs multilayers

Abstract: The growth terraces in molecular beam epitaxy-grown AlxGa1−xAs multilayers are observed on the ultrahigh vacuum cleaved (110) cross-sectional plane using scanning tunneling microscopy. Under regular growth conditions on 2° off oriented vicinal surfaces, we observe step bunching of 2–8 atomic layers and a corresponding extension of the terrace length instead of monolayer steps. These results demonstrate that the roughness of quantum confinement layers can be studied down to the atomic scale in a direct way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…These nanowires, unlike those grown on GaAs(100) or (110), are misoriented with respect to the substrate crystal lattice, so their orientations can be directly determined by finding their Bragg peaks. The orientation of [19,20], one of the factors the projection model did not consider, could affect the planar nanowire growth direction. However, it is not clear what caused the slight discrepancy between the calculated and measured growth directions at this point.…”
Section: Resultsmentioning
confidence: 99%
“…These nanowires, unlike those grown on GaAs(100) or (110), are misoriented with respect to the substrate crystal lattice, so their orientations can be directly determined by finding their Bragg peaks. The orientation of [19,20], one of the factors the projection model did not consider, could affect the planar nanowire growth direction. However, it is not clear what caused the slight discrepancy between the calculated and measured growth directions at this point.…”
Section: Resultsmentioning
confidence: 99%
“…Salemink et al. performed the first studies in which a GaAs/Al x Ga 1 - x As heterojunction interface was resolved directly by scanning tunneling spectroscopy, and subsequently extended this work to obtain the first atomically resolved images of GaAs/Al x Ga 1 - x As heterostructures. To date, a number of groups have reported scanning tunneling microscopy studies, both in air and under ultrahigh-vacuum conditions, of epitaxially grown structures in a wide range of material systems.…”
Section: Iii−v Semiconductor Characterizationmentioning
confidence: 99%
“…Cross-sectional STM offers unique capabilities for characterization of atomic-scale structure in semiconductor alloy layers and at heterojunction interfaces. It has been noted , that because STM imaging is sensitive primarily to the one or two uppermost layers on the surface, atomic-scale features in structure and electronic properties can be resolved with considerably greater detail than in other techniques. High-resolution X-ray diffraction can in some circumstances yield information about atomic-scale interface structure in superlattices, , but this information is inevitably averaged over many layers and also over a large area of the sample.…”
Section: A Electronically Induced Topographic Contrastmentioning
confidence: 99%
“…A common feature of STM-images of Al x Ga 1Àx As(1 1 0) obtained at relatively large bias voltage (2.0-2.5 V) is that for filled-states images, the alloy-related minima appear between the atomic rows, whereas for the empty-states images, they appear centered on the atomic rows [1,6,9]. In Figs.…”
Section: Comparison Between Filled-and Empty-states Images Of Algaasmentioning
confidence: 97%
“…One reason to study Al x Ga 1Àx As-{1 1 0} by STM is to learn about the way the Al-atoms are distributed within the crystal, and in what ways this distribution might be affected by details of its epitaxial growth [3,[7][8][9]. For this type of study it is essential that individual Al-atoms can be identified in the STM-image.…”
Section: Introductionmentioning
confidence: 98%